Impact of variations of gravitational acceleration on the general circulation of the planetary atmosphere. (January 2017) - Kilic, Cevahir; Raible, Christoph C.; Stocker, Thomas F.; Kirk, Edilbert
Abstract: Fundamental to the redistribution of energy in a planetary atmosphere is the general circulation and its meridional structure. We use a general circulation model of the atmosphere in an aquaplanet configuration with prescribed sea surface temperature and investigate the influence of the gravitational acceleration g on the structure of the circulation. For g = g 0 = 9.81 m s − 2, three meridional cells exist in each hemisphere. Up to about g / g 0 = 1.4 all cells increase in strength. Further increasing this ratio results in a weakening of the thermally indirect cell, such that a two- and finally a one-cell structure of the meridional circulation develops in each hemisphere. This transition is explained by the primary driver of the thermally direct Hadley cell: the diabatic heating at the equator which is proportional to g . The analysis of the energetics of the atmospheric circulation based on the Lorenz energy cycle supports this finding. For Earth-like gravitational accelerations transient eddies are primarily responsible for the meridional heat flux. For large gravitational accelerations, the direct zonal mean conversion of energy dominates the meridional heat flux. Abstract : Highlights: The planet's gravity determines the meridional structure of atmospheric circulation. An energy cycle analysis reveals the major drivers of the atmospheric circulation. With increasing gravity the meridional circulation changes from 3 cells to 1 cell.